Relentless spread and adaptation of non-typeable vanA vancomycin-resistant Enterococcus faecium: a genome-wide investigation. (16th March 2018) - van Hal, Sebastiaan J; Beukers, Alicia G; Timms, Verlaine J; Ellem, Justin A; Taylor, Peter; Maley, Michael W; Newton, Peter J; Ferguson, John K; Lee, Andie; Chen, Sharon C -A; Sintchenko, Vitali
Abstract: Background: VRE are prevalent among patients in ICUs. Non-typeable vanA VRE, due to loss of one of the genes used for MLST ( pstS ), have increased in Australia, suggestive of a new, hospital-acquired lineage. Objectives: To understand the significance of this lineage and its transmission using WGS of strains isolated from patients in ICUs across New South Wales, Australia. Methods: A total of 240 Enterococcus faecium isolates collected between February and May 2016, and identified by conventional PCR as vanA positive, were sequenced. Isolates originated from 12 ICUs in New South Wales, grouped according to six local health districts, and represented both rectal screening swab ( n  =   229) and clinical ( n  =   11) isolates. Results: ST analysis revealed the absence of the pstS gene in 84.2% (202 of 240) of vanA isolates. Two different non-typeable STs were present based on different allelic backbone patterns. Loss of the pstS gene appeared to be the result of multiple recombination events across this region. Evidence for pstS -negative lineage spread across all six local health districts was observed suggestive of inter-hospital transmission. In addition, multiple outbreaks were detected, some of which were protracted and lasted for the duration of the study. Conclusions: These findings confirmed the evolution, emergence and dissemination of non-typeable vanA E. faecium . This study has highlighted the utility of WGS when attempting to describe accurately the hospital-based pathogen epidemiology, which in turn will continue to inform optimal infection control measures necessary to halt the spread of this important nosocomial organism.